Feasibility Study on Establishment of Ice Bang in North Fairview Corner Regalado Street, Greater Lagro, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Ice cream is a sweetened frozen food that is typically eaten as a snack or dessert. Ice Bang is a store that offers ice cream flavors as a snack or dessert made from different vegetables, such as bitter gourd, carrot, chili, squash, and tomato. The researchers decided on this concept because one of the researchers is a fan of ice cream; they wanted to satisfy health-conscious customers. Ice cream is a good stress reliever, and ice cream shop is a large and growing industry in the Philippines. This ice cream was established in October 2019 and is located at North Fairview, Corner Regalado and Lagro with the capital of PHP 1,000,000 and has four employees. The research method used the descriptive method to determine the viability of the business. This study also used SWOT analysis to build on what the business does well, address what the business lacks, and take the best possible advantage of chances for success. The researchers used a survey questionnaire wherein the researchers surveyed 50 respondents to collect data and inform the researchers about the findings. The researchers used the information from the questionnaires, including the price, product, place, and promotion of the business, as basis for data analysis. Lastly, the researchers analyzed the financial statement to evaluate the company’s performance and estimate future risks and potential. The results of the study identified the market viability of the business concept and the number of employees of the company. The business is also classified as a general partnership. In terms of gender, female customers are considered the primary target of the business. In terms of age, the range of 19–25 years old is the primary target market, including students and employees. In terms of occupation, the primary target market is students. Under the average condition, the business is expected to have a return on investment in the 2nd year of the operation with the amount of PHP 428,794. The researchers recommend the business enhance ice cream flavors by creating a new flavor that will satisfy customers’ needs at an affordable price. The business should also expand by retailing to partner with convenience stores for customers far from the main branch of Ice Bang. The income statement, cash flow, and balance sheet showed that the business is feasible in terms of its pricing because the products it offers have affordable prices.
Keywords: feasibility study, establish, ice cream